PENGARUH GURU PENDIDIKAN AGAMA KRISTEN TERHADAP PELAYANAN REMAJA DALAM KONTEKS GEREJA DI INDONESIA (THE INFLUENCE OF CHRISTIAN RELIGION EDUCATION TOWARD TEENAGERS SERVICES IN THE CONTEXT OF CHURCHES IN INDONESIA) - Yoseti Gulo; Widjaja Sugiri (Widya Agape School of Theology and Indonesia Christian Theologians Association, 2020)
Facing the development of science and technology, Christian Religious Education provides an understanding for adolescents to utilize technology and stay away from its negative effects. The mission of Christian Religious Education means to provide a comprehensive change in spiritual life in the midst of a pluralistic society. Therefore, Christian Religious Education teachers in the church must be sensitive to the conditions, development and needs of youth. This study aims first, to improve the professional competence of Christian Religious Education teachers in churches to foster Christian values for Christian teenagers. Second, Christian Religious Education teachers realize that the growth of adolescent faith helps build good and appropriate teenagers levels. Third, Christian teenagers will take part in the ministry when they become mature in faith by using descriptive qualitative methods. Menghadapi perkembangan ilmu pengetahuan dan teknologi, Pendidikan Agama Kristen berperan memberikan pemahaman bagi remaja untuk memanfaatkan teknologi dan menjauhi dampak negatifnya. Misi Pendidikan Agama Kristen ialah memberikan perubahan kehidupan rohani yang menyeluruh ditengah-tengah masyarkat majemuk. Karena itu, guru Pendidikan Agama Kristen di gereja harus peka terhadap kondisi, perkembangan dan kebutuhan remaja. Penelitian ini bertujuan pertama, meningkatkan kompetensi profesional guru Pendidikan Agama Kristen di gereja untuk menumbuhkan nlai-nilai kristiani remaja Kristen. Kedua, guru Pendidikan Agama Kristen menyadari bahwa pertumbuhan iman remaja turut dipengaruhi oleh pengajaran yang baik dan tepat sesuai level remaja. Ketiga, remaja Kristen akan mengambil bagian dalam pelayanan ketika sudah menjadi dewasa iman dengan menggunakan metode kualitatif deskriprif.